Evaluation of the Impact of Different Surface Treatments on Implant Surface: An In Vitro Study - Subramanian Deepa; Mathew Joel; Mailankote Shilpa; Almuraikhi Turki; Daghriri Alhussain (Wolters Kluwer Medknow Publications, 2024)
AimThe current study was conducted to assess the effects of various surface treatments on the implant surface. Materials and MethodsA total of 45 dental implants measuring 16 mm in length and 5 mm in diameter were used, along with the appropriate abutments. Depending on the surface treatment used, the samples were randomly split into three groups, with 15 implants in each group: Group 1: Control, Group 2: UV light-treated, Group 3: Sandblasted and acid-etched (SLA)-treated. After surface treatment, a scanning electron microscope (SEM) was used to assess the test samples' surface properties. All sample images were captured using a 3000× magnification. After all three groups' surfaces were treated, the surface roughness was measured using a digital optical profilometer with a stylus speed of 0.5 mm/s that was connected to computer software. ResultsThe maximum surface roughness was found in the group treated with SLA (0.714 ± 0.12), followed by the group treated with UV light (0.692 ± 0.09) and the control group (0.516 ± 0.12). There was a significant difference found between different surface treatment methods. ConclusionThe present study concluded that the group that received the SLA treatment had the highest surface roughness when compared to the UV light and control groups.